2004
DOI: 10.2193/0091-7648(2004)32[542:srmcah]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates, mortality causes, and habitats of Pennsylvania white-tailed deer fawns

Abstract: Estimates of survival and cause‐specific mortality of white‐tailed deer (Odocoileus virginianus) fawns are important to population management. We quantified cause‐specific mortality, survival rates, and habitat characteristics related to fawn survival in a forested landscape and an agricultural landscape in central Pennsylvania. We captured and radiocollared neonatal (<3 weeks) fawns in 2000–2001 and monitored fawns from capture until death, transmitter failure or collar release, or the end of the study. We es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
152
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(160 citation statements)
references
References 38 publications
7
152
1
Order By: Relevance
“…For summer calf encounter histories (n ¼ 116), we used 1-week intervals to record radiotagging, survival, mortality, and censor events. We left-justified calf histories, so survival estimates related to calf survival by weeks irrespective of the actual date calves were radiotagged (Vreeland et al 2004, Raithel 2005. We first modeled constant summer survival through 20 weeks.…”
Section: Survival Analysesmentioning
confidence: 99%
“…For summer calf encounter histories (n ¼ 116), we used 1-week intervals to record radiotagging, survival, mortality, and censor events. We left-justified calf histories, so survival estimates related to calf survival by weeks irrespective of the actual date calves were radiotagged (Vreeland et al 2004, Raithel 2005. We first modeled constant summer survival through 20 weeks.…”
Section: Survival Analysesmentioning
confidence: 99%
“…Ample evidence exists in the literature demonstrating that coyote predation on white-tailed deer (Odocoileus virginianus), particularly neonatal fawns, can be high (e.g., Cook et al 1971, Bartush and Lewis 1981, Whittaker and Lindzey 1999, Vreeland et al 2004. After reviewing this literature, Ballard et al (2001) concluded that coyotes can be a significant mortality factor for deer, and Ballard et al (1999) suggested that coyotes have replaced wolves in their role as deer predators in parts of northeastern North America, frequently taking adults during winter as well as neonatal fawns.…”
mentioning
confidence: 99%
“…Studies that have continued to monitor radiomarked fawns past the first 8 weeks of life have attributed older fawn mortalities to hunting, poaching, and vehicle collisions (Vreeland et al 2004; Rohm et al 2006;Burroughs et al 2006;Hiller et al 2007). Thus, another method for estimating deer vital rates is by analyzing deer harvest data (e.g., fawn-to-doe kill ratios, age structure of harvest).…”
Section: Introductionmentioning
confidence: 99%